2013
DOI: 10.1177/0022185613489398
|View full text |Cite
|
Sign up to set email alerts
|

Unionism and non-union employee representation: The interwar experience in Canada, Germany, the US and the UK

Abstract: The decline in trade union membership in a number of countries has led to concerns over a ‘representation gap’, where workers are deprived of a voice not only in regard to their workplace grievances, but also in regard to their contributions to productivity and the quality of working life. While a number of alternatives have been raised, including joint consultation and works councils, there are concerns that these alternatives may further weaken union organization by establishing rival forms of organization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the Italian context, such labour movements – backed by the socialist party – generated a period of social instability (1919-1920) characterised by mass strikes and factory occupations (Cinquini, 2007). In the USA, as Kaufman (2014, 2015), Patmore and Rees (2008) and Patmore (2013) have shown, many large employers responded to such problems by initiating workplace and community welfare programmes that they hoped would restore industrial and social order within their businesses and operating environment. A study of 1,600 large US plants, carried out in 1927, found that 24 per cent operated company hospitals, 26 per cent provided employee pension schemes and 43 per cent organised company sporting and athletic programmes (Kaufman, 2015, p. 199).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Italian context, such labour movements – backed by the socialist party – generated a period of social instability (1919-1920) characterised by mass strikes and factory occupations (Cinquini, 2007). In the USA, as Kaufman (2014, 2015), Patmore and Rees (2008) and Patmore (2013) have shown, many large employers responded to such problems by initiating workplace and community welfare programmes that they hoped would restore industrial and social order within their businesses and operating environment. A study of 1,600 large US plants, carried out in 1927, found that 24 per cent operated company hospitals, 26 per cent provided employee pension schemes and 43 per cent organised company sporting and athletic programmes (Kaufman, 2015, p. 199).…”
Section: Methodsmentioning
confidence: 99%
“…Interest in “welfare capitalism” gained further ground in the USA following the so-called “Ludlow massacre” in April 1914, when armed conflict erupted between striking coal miners and management on the Colorado coalfields. This conflict turned the principal coal owner, John Rockefeller, Jr, into an ardent advocate of welfare programmes for workers and their families (Patmore, 2013; Patmore and Rees, 2008). After these pioneering initiatives, more followed, promoted by US companies such as Kodak, General Electric, International Harvester, Proctor and Gamble, AT&T, Goodyear and Leeds & Northrup (Kaufman, 2015, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other labor relations experts question whether employee work groups offer a path to negotiation and contractual relationships, even in countries generally amenable to collective action. Patmore (2013) observes that the debate over non-union employee representation, or NUER, remains inconclusive. He notes:…”
Section: Introductionmentioning
confidence: 99%